Kinking in Semiconductor Nanowires: A Review - Vlassov, Sergei; Oras, Sven; Polyakov, Boris; Butanovs, Edgars; Kyritsakis, Andreas; Zadin, Veronika (American Chemical Society, 2022)
The growth direction of nanowires (NWs) can change during synthesis as a result of stochastic processes or modulation of certain growth conditions. This phenomenon is known as kinking. Although deviations from a uniform vertical growth are typically considered to be undesirable, kinking opens a route for additional tweaking of the characteristics and functionalities of NWs in a controllable manner, thus extending the range of potential applications. In the present Review, we give an insight into the kinking mechanisms and summarize the most crucial factors that can lead to kinking of NWs during synthesis. Additionally, the properties and applications of kinked NWs are discussed. © 2021 The Authors. Published by American Chemical Society. Published under the CC BY 4.0 and CC BY-NC-ND 4.0 licenses.
Keywords: Research Subject Categories::NATURAL SCIENCES